2020
DOI: 10.2147/ijn.s266514
|View full text |Cite
|
Sign up to set email alerts
|

<p>Design and Fabrication of Dual Redox Responsive Nanoparticles with Diselenide Linkage Combined Photodynamically to Effectively Enhance Gene Expression</p>

Abstract: Background PEI is currently the most used non-viral gene carrier and the transfection efficiency is closely related to the molecular weight; however, the prominent problem is that the cytotoxicity increased with the molecular weight. Methods A novel redox responsive biodegradable diselenide cross-linked polymer (dPSP) was designed to enhance gene expression. ICG-pEGFP-TRAIL/dPSP nanoparticles with high drug loading are prepared, which have redox sensitivity and plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Recently, the ROS/GSH dual‐responsive property of diselenide has been introduced in polymer nucleic acid vector for more efficient cancer therapy. Fang et al [ 401 ] reported a high molecular weight polymer dPSPs synthesized through crosslinking endogenous spermine by diselenide, which exhibited complete DNA compression, low cytotoxicity, and ideal proton buffering effect. Next, therapeutic pDNA and photosensitizer indocyanine green (ICG) were loaded in the synthesized polymeric vector to synthesize the polyplexes.…”
Section: Redox‐responsive Polymeric Nps For Nucleic Acids Delivery In...mentioning
confidence: 99%
“…Recently, the ROS/GSH dual‐responsive property of diselenide has been introduced in polymer nucleic acid vector for more efficient cancer therapy. Fang et al [ 401 ] reported a high molecular weight polymer dPSPs synthesized through crosslinking endogenous spermine by diselenide, which exhibited complete DNA compression, low cytotoxicity, and ideal proton buffering effect. Next, therapeutic pDNA and photosensitizer indocyanine green (ICG) were loaded in the synthesized polymeric vector to synthesize the polyplexes.…”
Section: Redox‐responsive Polymeric Nps For Nucleic Acids Delivery In...mentioning
confidence: 99%